Design and development of ultra wideband (UWB) antenna (planar triangular monopole antenna) - Wan Sabrina Wan Long
This final year project proposes an omnidirectional UWB antenna pattern in azimuth cut and easy to construct antenna for ultra wideband (UWB) systems.